Predictors of Stress from Online Learning among Pharmacy Students - Poolthong, Angkana; Duangrithi, Duangjai (Srinagarind Medical Journal, 2022)
Background and Objective: Measure and monitoring of pandemic of COVID 19 issue 10 stated that institutions of higher education must arrange the distance or electronic learning. The COVID 19 situations as well as rapid change in learning make the students worrisome. Methods: This survey study was conducted in 1st to 5th year pharmacy students to explore the predicting factors of harmful stress and the predicting factors of negative solution. The data was collected by online questionnaire during January to February 2021. Results: Of 322 students, the average age was 20.87 years old. The student with the harmful stress reported the problems of learning (77.40 vs 32.20, p<0.001) and the worry of their future (76.60 vs 26.40, p<0.001) as the most common causes. The predicting factors of harmful stress were long learning period (OR=4.56; 95%CI=2.22-9.37) similar to the expense for online learning (OR=4.51; 95%CI=1.62-12.55). In addition, the predicting factors of negative solution was age<20 years old (OR=0.52; 95%=0.36-0.75). Conclusions: Suitable online learning format for students and continuing quality development in online teaching can lead to qualified learning and reducing student stress.